2021
DOI: 10.1002/ijc.33721
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of pemetrexed during renal impairment explained—Implications for safe treatment

Abstract: Pemetrexed is an important component of first line treatment in patients with non‐squamous non‐small cell lung cancer. However, a limitation is the contraindication in patients with renal impairment due to hematological toxicity. Currently, it is unknown how to safely dose pemetrexed in these patients. The aim of our study was to elucidate the relationship between pemetrexed exposure and toxicity to support the development of a safe dosing regimen in patients with renal impairment. A population pharmacokinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The following parameters (lower limit; upper limit) were included in the sensitivity analyses: medication costs during admission (lower and upper limit determined in this study), costs of one extra WBC (lower and upper limit determined in this study), interindividual variability (IIV) of baseline eGFR (CV 16% as this is found in the study of de Rouw et al . 32 ; upper limit was not tested as a higher IIV is not found in previous studies), and IIV of baseline ANC (CV 30%; CV 45% 29 ).…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations
“…The following parameters (lower limit; upper limit) were included in the sensitivity analyses: medication costs during admission (lower and upper limit determined in this study), costs of one extra WBC (lower and upper limit determined in this study), interindividual variability (IIV) of baseline eGFR (CV 16% as this is found in the study of de Rouw et al . 32 ; upper limit was not tested as a higher IIV is not found in previous studies), and IIV of baseline ANC (CV 30%; CV 45% 29 ).…”
Section: Methodsmentioning
confidence: 94%
“…The model is described in detail by Boosman et al . 29 A population of 500 participants was simulated for each scenario. Weights and heights were derived from the National Health and Nutrition Examination Survey (NHANES) database (median body mass index = 26.2 kg/m 2 , comparable to baseline body mass index of patients with lung cancer 30 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the development of an analytic method has proven to be challenging [106]. Although it is unclear how well the polyglutamylated forms of pemetrexed correlate to pemetrexed plasma concentrations, a plasma exposure-toxicity relationship has been well-established in a generally broad range of doses (126-1362 mg) [107][108][109]. In addition, doses of pemetrexed 900-1000 mg/m 2 did not improve efficacy of treatment compared with standard dosing of 500 mg/ m 2 Q3W [110].…”
Section: Pemetrexedmentioning
confidence: 99%